The Landscape of Verbal Abuse of Adolescent Students in Indonesia: A Comparative Study Based on Gender and Region - Muh. Syawal Hikmah; IM Hambali; Adi Atmoko (GUIDING WORLD (BIMBINGAN DAN KONSELING), 2026)
This study aims to analyze the landscape of verbal abuse among adolescents in Indonesia and examine its differences based on gender and region. This study used a quantitative approach with a comparative design. The study subjects were 308 junior high school (SMP/MTs) and senior high school (SMA/SMK) students aged 12–18 years from East Java (Malang Raya) and South Sulawesi (Makassar city, Bulukumba, Gowa, dan Palopo city) consisting of 154 male students and 154 female students. The sampling technique used was purposive sampling. Data collection was conducted using the Indonesian adaptation of the Indonesian Verbal Abuse Questionnaire (I-VAQ), which covers seven aspects: verbal aggression, blaming, insults/name-calling, threats, shaming, negative criticism, and self-deprecation. The instrument demonstrated good reliability with a Cronbach's alpha value of 0.897. Data analysis was conducted descriptively and inferentially using the Mann-Whitney U test. The results showed that verbal abuse among adolescents was generally in the moderate category. There was a significant difference based on gender (p = 0.042), with the mean score of males being higher than that of females. Furthermore, significant differences were found based on region (p < 0.001), with the average verbal abuse score for adolescents in East Java being higher than in South Sulawesi. This finding confirms that verbal abuse in adolescents needs to be understood contextually, taking into account gender and regional factors as a basis for developing more sensitive and targeted guidance and counseling interventions